Dichotomy in pulmonary graft-versus-host disease evident among allogeneic stem-cell transplant recipients undergoing lung transplantation. Issue 6 (1st September 2016) - Greer, Mark; Riise, Gerdt C.; Hansson, Lennart; Perch, Michael; Hämmäinen, Pekka; Roux, Antoine; Hirschi, Sandrine; Lhuillier, Elodie; Reynaud-Gaubert, Martine; Philit, Francois; Claustre, Johanna; Stern, Marc; et al.
Allogeneic haematopoietic stem-cell transplantation (HSCT) has become a life-saving treatment option for numerous benign and malignant diseases, with more than 14 500 procedures being performed annually in Europe alone [1]. Late-onset noninfectious pulmonary complications (NIPCs) have emerged as the main hurdle to long-term survival, affecting up to 26% of HSCT recipients and conferring 2- and 5-year survival rates of 44% and 13%, respectively [2, 3]. Interstitial lung disease is a common, largely unrecognised feature of pulmonary GvHD after stem cell transplant http://ow.ly/Tnx83034yR0